NILAI-NILAI DALAM AKTUALISASI PENINGKATAN KARAKTER KEPEDULIAN LINGKUNGAN MAHASISWA - La Ode Nursalam; Eko Harianto; Muhammad Hasan; Andri Estining Sejati (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2019)
Abstract The basic values of the State Civil Apparatus (ASN) consist of accountability, nationalism, public ethics, quality commitment, and anti-corruption. The position and role of ASN in the Republic of Indonesia consists of ASN management, the Whole of Government and Public Services. The basic values, roles, and position must be reflected in the issue of solving activities in the basic training activities of the Ministry of Research, Technology and Higher Education. This type of research is a pre-experimental paper with the subject of Udergraduate Geography Education 2016 class. Actualization was carried out from 16 August to 20 November 2018 at USN Kolaka. Activities on campus include: 1) carrying out environmental awareness counseling for students 2) implementing the environmental care integrity pact. 3) GIS training on environmental studies. Off campus activities include: 1) planting trees in the campus environment of USN Kolaka, 2) cleaning the gutters in the campus environment of USN Kolaka, 3) counseling and outreach activities to the community are adapted into environmental awareness counseling by students and lecturers to students in other majors (Mathematics Education). The research instruments were self evaluation, pretest and posttest. Self evaluation data were analyzed descriptively. While the pretest and posttest data were analyzed using parametric inferential statistics through one sample t-test with the help of SPSS 16.0 for Windows. The results of data analysis showed that there was an influence of Basic Training on the characters of environmental awareness of students with the significance value of testing one sample t-test with the help of SPSS 16.0 for Windows of 0,000. All activities nuanced basic values, roles and positions of ASN in the Homeland.Keywords: basic training, character, environment awareness AbstrakNilai-nilai dasar Aparatur Sipil Negara (ASN) terdiri dari akuntabilitas, nasionalisme, etika publik, komitmen mutu, dan anti korupsi. Kedudukan dan peran ASN dalam NKRI terdiri dari manajemen ASN, Whole of Government dan Pelayanan Publik. Nilai dasar, peran, dan kedudukan tersebut wajib tercermin dalam kegiatan pemecahan isu pada kegiatan pelatihan dasar Kementristek Dikti. Jenis penelitian makalah adalah pre eksperimen dengan subjek mahasiswa S1 Pendidikan Geografi Kelas 2016. Aktualisasi dilakukan dari 16 Agustus hingga 20 November 2018 di USN Kolaka. Kegiatan on campus meliputi: 1) melaksanakan penyuluhan peduli lingkungan kepada mahasiswa 2) penerapan pakta integritas peduli lingkungan. 3) Pelatihan SIG kajian lingkungan. Kegiatan off campus meliputi: 1) penanaman Pohon di lingkungan kampus USN Kolaka, 2) Pembersihan Selokan di lingkungan kampus USN Kolaka, 3) kegiatan penyuluhan dan sosialisasi ke masyarakat diadaptasi menjadi penyuluhan kepedulian lingkungan oleh mahasiswa dan dosen ke Mahasiswa jurusan lain (S1 Pendidikan Matematika). Instrumen penelitian adalah self evaluation, pretest dan posttest. Data self evaluation dianalisis dengan deskrriptif. Sedangkan data pretest dan posttest dianalisis menggunakan statistik inferensial parametrik melalui uji satu sampel t-tes dengan bantuan SPSS 16.0 for Windows. Hasil analisis data menunjukkan bahwa ada pengaruh Pelatihan Dasar pada karakter karakter kesadaran lingkungan siswa dengan nilai signifikansi pengujian satu sampel t-test dengan bantuan SPSS 16.0 for Windows sebesar 0.000. Seluruh kegiatan bernuansa nilai dasar, peran, dan kedudukan ASN dalam NKRI.Kata Kunci: pelatihan dasar, karakter, kepedulian lingkungan